Proceedings of the First International Conference on Gameful Design, Research, and Applications 2013
DOI: 10.1145/2583008.2583011
|View full text |Cite
|
Sign up to set email alerts
|

Using gamification to inspire new citizen science volunteers

Abstract: Gamifying citizen science campaigns has the potential to further engage existing volunteers, as well as to attract new contributors. By evaluating Biotracker, a gamified mobile application that gathers plant phenology data, we explored the feasibility of engaging a secondary group of Millennials, who are notorious technology enthusiasts, with a gamified citizen science app. We also explored the potential benefits that using an application might offer these users. Results suggest that gamification is key to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 20 publications
5
95
0
11
Order By: Relevance
“…While points and rankings were considered to be key features for enjoyment by Foldit players, they were perceived as creating competition but not fun by GZ participants. This finding is consistent with previous studies which found that the same competitive mechanisms can be rewarding for some and demotivating for others (Eveleigh et al 2013;Bowser et al 2013;Preist et al 2014). For example, previous results found that when leaderboards were used by participants to compare with what others were doing, they were motivating for high-scoring participants, but off-putting for low-scoring participants who felt they could not catch up (Preist et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While points and rankings were considered to be key features for enjoyment by Foldit players, they were perceived as creating competition but not fun by GZ participants. This finding is consistent with previous studies which found that the same competitive mechanisms can be rewarding for some and demotivating for others (Eveleigh et al 2013;Bowser et al 2013;Preist et al 2014). For example, previous results found that when leaderboards were used by participants to compare with what others were doing, they were motivating for high-scoring participants, but off-putting for low-scoring participants who felt they could not catch up (Preist et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…When there are no hobbies to leverage in a project (birdwatching is an example of a hobby leveraged in citizen science), games can produce the same sense of fun and enjoyment as "real world" activities while still successfully linking participants to data collection efforts (Prestopnik and Crowston 2012). While some studies have found the prevalence of intrinsic reasons in motivating volunteers in online citizen science projects, other studies suggest that extrinsic reasons drive engagement as well, especially in a game-based project (Bowser et al 2013, Rotman et al 2012). These different results should not be seen as contradicting each other as they reflect the diversity of online citizen science projects and of people participating (or not participating) in them (Tinati et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gamification has emerged on to the VCS scene partly due to cheaper technology, but also thanks to personal data tracking and the familiarity people now have with 'games' as a medium [Deterding 2012;Seaborn and Fels 2015]. There is already a growing body of literature discussing the merits and advantages of gamification in individual citizen science projects, with findings suggesting increased success in attracting Millennials, and end-results such as increased community awareness [Bowser et al 2013]. However, despite the generally well-received nature of gamification, studies have suggested that certain aspects of it may turn away certain participants-for example in the Old Weather project there appears to be a disparity between those participants who are driven to compete thanks to the use of certain mechanisms, and those more casual users who ignore them or, in some cases, decided to completely withdraw from the project [Eveleigh et al 2013].…”
Section: Gamification In Virtual Citizenmentioning
confidence: 99%
“…Even among those players who are more extrinsically motivated, Siu and Riedl [2016] describe that gaming alone was insufficient to overcome the boredom associated with repetative human computation tasks, particularly where players derived fun from collecting extrinsic factors such as game unlockables. On the other hand, Bowser et al [2013] suggest that reward-based game elements such as badges are associated with player interest and enjoyment and that as a result, these features do in fact increase the motivation to participate.…”
Section: Participant Motivationmentioning
confidence: 99%
“…There are a number of serious games types such as educational games, commercial games, training games, and so forth. They can be used to train professionals (Wattanasoontorn et al, 2013;Graafland et al, 2012;Kapp, 2012), to help learning process (Chowanda & Prasetio, 2012;Chowanda et al, 2014;Kapp, 2012), to educate the public (Bowser et al, 2013), make the public aware of a new product (Huotari & Hamari, 2011;Rampoldi-Hnilo & Snyder, 2013). Schell (2014) argues that it requires four core elements to craft a game.The first is Mechanics, a set of procedures or rules in a game.…”
Section: Introductionmentioning
confidence: 99%